Comparing the effects of Cyperus esculentus hydroethanolic extract and Euterpe oleracea on reproductive efficacy against cadmium-induced testicular toxicity in male rats (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Cadmium chloride (CdCl2 ) is an environmentally toxic pollutant that can cause reprotoxicity. Cyperus esculentus and Euterpe oleracea are potent antioxidant plants currently used to counteract the action of harmful pollutants. The present experiment was intended to evaluate and comp are the role of C. esculentus hydroethanolic extract (CHE) and E. oleracea in treating the reprotoxicity induced by CdCl2 in rats. Materials and Methods: Forty adult male rats (160–210 gm) were allocated into five groups equally. Control group: received 5 ml of normal saline (NS); the other treatment groups were injected with CdCl2 as a single dose for two weeks to induce testicular toxicity. After 14 days, the four groups were treated orally daily for two months as follows: The cadmium group (Cd) received NS, the third group (TC) was administered 800 mg/kg BW of CHE, the fourth group (TO) received 500 mg/kg BW of E. oleracea, and the fifth group (TCO) received CHE with E. oleracea. Results: The live sperm and motility, serum testosterone, follicle-stimulating hormone (FSH), testicular superoxide dismutase (SOD), catalase (CAT), steroidogenic acute regulatory protein (StAR), 17β-hydroxysteroid dehydrogenase, and 3β-hydroxysteroid dehydrogenase (3β-HSD) were significantly increased in the TCO, TC, and TO groups compared with the Cd group. Testicular nitric oxide and malondialdehyde were elevated significantly in the Cd group compared to the TC, TO, TCO, and control groups. The fold changes of Fshβ, Lhβ, and Gnrh genes were upregulated in the TCO group compared to the Cd and control groups. Conclusion: The combination of CHE with E. oleracea showed improvements in rat testicles affected by cadmium toxicity via upregulated reproductive gene expression and its antioxidant effects.J. Adv. Vet. Anim. Res., 10(4): 685–695, December 2023http://doi.org/10.5455/javar.2023.j724